Unruly subjects: The subaltern struggle for media justice, multimodality, and autoethnography in academia and beyond - Osman, Wazhmah (Visual anthropology review, 2024)
In this autoethnographic article, I explore the “crisis of representation” and the struggle of subaltern people for reparative representation and media justice. I argue that the field of visual anthropology and its multimodal programs have emerged from the margins to be at the forefront of decolonizing media and representation in the academy and beyond, but more work still needs to be done to achieve parity. I highlight the work and programs of leading scholar‐practitioners and their methodological and theoretical approaches that have shifted the paradigm of modern anthropology and representational politics and practice more generally. I focus on the trajectory of Faye Ginsburg's scholarship and media activism working with Indigenous, disability, and reproductive justice movements and show its impact on my work in the media worlds of the United States and Afghanistan and on Middle Eastern and Asian contexts and studies more broadly.